Life cycle greenhouse gas emissions of conventional and alternative steel production methods in countries dependent on energy import: A South Korean case study - Juha Lee; Gyuna Kwak; Yujin Jung; Wonjae Choi (Energy Conversion and Management: X)
This study used a life cycle assessment to quantitatively compare greenhouse gas emissions among traditional coal blast furnaces and alternative methods such as hydrogen direct reduction, natural gas direct reduction, and electric arc furnaces. Greenhouse gas (GHG) emissions were calculated throughout the life cycle of producing 1 ton of liquid steel (tLS) in countries dependent on energy imports through maritime transportation. The life cycle assessment results for these countries differs from those of countries capable of land-based transportation. In particular, when transporting gaseous fuels such as natural gas and hydrogen via maritime routes, liquefaction process emits a substantial GHG emissions, ultimately leading to higher life cycle GHG emissions in steel production. Therefore, this study conducted a case study on South Korea, a representative steel-producing country that relies on maritime transportation for energy imports. The analysis employed the GREET program developed by the Argonne National Laboratory in the United States, modified and expanded to reflect the Korean context. The data used in the analysis was selected through a literature review and thermodynamic modeling of the process. The life cycle assessment revealed that, coal blast furnaces emit 1612 kg-CO2-eq./tLS, natural gas direct reduction emits 1435 kg-CO2-eq./tLS, hydrogen direct reduction using domestically produced blue hydrogen emits 961 kg-CO2-eq./tLS, and electric arc furnaces emit 370 kg-CO2-eq./tLS. The electric arc furnace method, which utilizes steel scrap, emits the fewest greenhouse gases as it doesn’t need the reduction process. Depending on the method of hydrogen production, the values for hydrogen direct reduction of iron ranged from 741 kg-CO2-eq./tLS to 2352 kg-CO2-eq./tLS, highlighting the significant impact of hydrogen production methods on the results. The variation in the life cycle of greenhouse gas emissions throughout the process was substantial depending on the electricity production method employed. Excluding coal blast furnaces, which utilizes minimal electricity externally supplied, it was observed that natural gas direct reduction, hydrogen direct reduction, and electric arc furnaces are significantly influenced by the electricity production method. When natural gas direct reduction utilizes coal-based power compared to renewable energy, it emits 2 times more the life cycle of greenhouse gas emissions. Hydrogen direct reduction uses coal-based power compared to renewable power emits 3.2 times more. Furthermore, sensitivity analysis was conducted on variables used in each steelmaking method. Confirmed was a variance in results of up to 4.5 % due to a 5 % fluctuation in the consumption of primary fuels such as coal, hydrogen, natural gas, and electricity. The other factors, excluding energy consumption exerted minimal influence, with variations below 0.5 %. The validity of energy consumption was confirmed to be appropriate based on literature and theoretical calculations used in this study. This suggests that the findings of this study are robust.